Women in modern Burma - Than, Tharaphi (Abingdon, Oxon : Routledge, 2014)
'Presents a comprehensive overview of the role of women in Burmese society from independence in 1948 to the present. It covers women in politics, women writers, working women, marginalised women such as prostitutes, and women's role in the 1940s as freedom fighters and since 1988 as campaigners for political reform. It shows how, although Burmese women project to the outside world an image of being strong, as exemplified by Aung San Suu Kyi, the leader of the opposition, women do not in fact enjoy gender equality'--
Print media and women journalists, editors, and writers -- Women's education -- The creation of the Burma Women's Army -- Disbanding the army and communist women -- Women and modernity -- Marginalized women in the making of the'Burman' nation.
Includes bibliographical references and index.
Keywords: Women -- Burma -- Social conditions -- 20th century; Women -- Burma -- Social conditions -- 21st century; Women's rights -- Burma -- History -- 20th century; Women's rights -- Burma -- History -- 21st century